Penggunaan YouTube Dalam Kajian Pembelajaran Bahasa Arab pada Mahasiswa PGMI - Ahmad Azhari; Danial Hilmi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2022)
This study aims to describe the steps taken by lecturers on the use of YouTube media in the Arabic Language Learning Study course and how students perceive YouTube media users in learning. This study uses descriptive qualitative methods. The instruments that researchers use in data collection are interviews, observations and documentation. The results of the study show, 1) YouTube is able to become an effective learning medium, especially in the current conditions that require distance learning. 2) Lecturers carry out learning with several steps, namely, a) delivery of material and questions and answers. b) Assignment. c) Evaluation. 3) Students gave positive responses to the use of YouTube as a medium of learning in Arabic learning study courses, provided that the media was easy, innovative and creative. Researchers hope that this research can add insight to teaching staff in making innovations in learning and making students more able to use social media in a more positive direction. This study aims to describe the steps taken by lecturers on the use of YouTube media in the Arabic Language Learning Study course and how students perceive YouTube media users in learning. This study uses descriptive qualitative methods. The instruments that researchers use in data collection are interviews, observations and documentation. The results of the study show, 1) YouTube is able to become an effective learning medium, especially in the current conditions that require distance learning. 2) Lecturers carry out learning with several steps, namely, a) delivery of material and questions and answers. b) Assignment. c) Evaluation. 3) Students gave positive responses to the use of YouTube as a medium of learning in Arabic learning study courses, provided that the media was easy, innovative and creative. Researchers hope that this research can add insight to teaching staff in making innovations in learning and making students more able to use social media in a more positive direction.